2018
DOI: 10.14202/vetworld.2018.1712-1719
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different smoking methods on the quality of pork sausages

Abstract: Aim:An experiment was conducted to evaluate the nutritional, physicochemical, microbiological, and sensory attributes of pork sausages treated with conventional smoking (CS) and liquid smoke (LS).Materials and Methods:Pork sausages were prepared by employing CS (T1) and by addition of LS at 3% (T2A), 5% (T2B), and 7% (T2C) while smoking was not done in control (C) sausages. The ready-to-eat pork sausages were evaluated in terms of proximate composition, emulsion stability (ES), cooking loss (CL), pH, water act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
2
11
0
3
Order By: Relevance
“…Bhuyan et al [ 32 ], analysing the impacts of various smoking methods on the quality of pork sausages, did not find statistically significant differences ( p ≥ 0.05) in terms of TPA parameters. The quoted authors showed higher values regarding the hardness, chewiness, cohesiveness and resilience in the case of hot smoked sausages.…”
Section: Resultsmentioning
confidence: 99%
“…Bhuyan et al [ 32 ], analysing the impacts of various smoking methods on the quality of pork sausages, did not find statistically significant differences ( p ≥ 0.05) in terms of TPA parameters. The quoted authors showed higher values regarding the hardness, chewiness, cohesiveness and resilience in the case of hot smoked sausages.…”
Section: Resultsmentioning
confidence: 99%
“…Heavy rainfall and less sunshine hours during monsoon (from June to October) in Goa forced the producers to adopt smoking of Goan pork sausages over sun drying. Traditional wood smoking also preserves the shelf life of Goan pork sausages due to the antimicrobial and antioxidant properties of the smoke components (Bhuyan et al, 2018;Lingbeck et al, 2014). Over some time, due to its rich sensory attributes and extended storage stability, the Goan pork sausage producers started producing more smoked versions than the sundried version.…”
Section: Purchase and Handling Behavior Of Consumersmentioning
confidence: 99%
“…The different methods of smoking process can result in a different shelf life of the product. Different smoking methods such as traditional hot smoking and fumigation using liquid smoke result in different shelf life (Bhuyan et al, 2018). Coconut shell liquid smoke which is traded consists of three grades.…”
Section: Introductionmentioning
confidence: 99%